Impulsive delayed reward discounting as a genetically-influenced target for drug abuse prevention: a critical evaluation - Gray, Joshua C.; MacKillop, James (Frontiers in Psychology, 2015)
This review evaluates the viability of delayed reward discounting (DRD), an index of how much an individual devalues a future reward based on its delay in time, for genetically-informed drug abuse prevention. A review of the literature suggests that impulsive DRD is robustly associated with drug addiction and meets most of the criteria for being an endophenotype, albeit with mixed findings for specific molecular genetic influences. Several modes of experimental manipulation have been demonstrated to reduce DRD acutely. These include behavioral strategies, such as mindfulness, reward bundling, and episodic future thinking; pharmacological interventions, including noradrengic agonists, adrenergic agonists, and multiple monoamine agonists; and neuromodulatory interventions, such as transcranial magnetic stimulation and transcranial direct current stimulation. However, the generalization of these interventions to positive clinical outcomes remains unclear and no studies to date have examined interventions on DRD in the context of prevention. Collectively, these findings suggest it would be premature to target DRD for genetically-informed prevention. Indeed, given the evidence of environmental contributions such as early life adversity to impulsive DRD, whether genetically-informed secondary prevention would ever be warranted is debatable. However, progress in identifying polymorphisms associated with DRD preference could further clarify the underlying biological systems implicated in impulsive DRD for further progress in pharmacological and neuromodulatory interventions. Furthermore, independent of genetically-informed prevention, impulsive DRD is a qualitatively different risk factor from existing prevention programs and is generally worthy of investigation as a novel and promising drug abuse prevention target.